2016
DOI: 10.1039/c5dt03283k
|View full text |Cite
|
Sign up to set email alerts
|

A chiral lanthanide metal–organic framework for selective sensing of Fe(iii) ions

Abstract: The preparation of a highly water stable and porous lanthanide metal-organic framework (MOF) nanoparticles (denoted SUMOF-7II; SU refers to Stockholm University) is described. SUMOF-7II was synthesized starting from the tritopic linker of 2,4,6-trip -carboxyphenyl pyridine (H 3 L2) and La(III) as metal clusters. SUMOF-7II forms a stable dispersion and displays high fluorescence emission with small variation over the pH range of 6 to 12. Its fluorescence is selectively quenched by Fe(III) ions compared to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(88 citation statements)
references
References 48 publications
8
80
0
Order By: Relevance
“…The results show that only a little amount of Cr 2 O 7 2− (CrO 4 2− ) ions in solution can be immobilized into the channels of NUM‐5 (Table S3) and this part of Cr VI (Cr 2 O 7 2− /CrO 4 2− ) has little quenching effect to the fluorescence intensity of NUM‐5 (Figure S13). Therefore, in this system, the adsorption amount of target anions is also not the determining factor for the observed fluorescence quenching behavior . The luminescence lifetimes of NUM‐5 before and after being immersed in Cr VI (Cr 2 O 7 2− /CrO 4 2− ) aqueous solutions are same, which indicated that there was no coordination effect between Cr VI ions and NUM‐5 (Figure S14).…”
Section: Stability Characterization Of Num‐5mentioning
confidence: 95%
“…The results show that only a little amount of Cr 2 O 7 2− (CrO 4 2− ) ions in solution can be immobilized into the channels of NUM‐5 (Table S3) and this part of Cr VI (Cr 2 O 7 2− /CrO 4 2− ) has little quenching effect to the fluorescence intensity of NUM‐5 (Figure S13). Therefore, in this system, the adsorption amount of target anions is also not the determining factor for the observed fluorescence quenching behavior . The luminescence lifetimes of NUM‐5 before and after being immersed in Cr VI (Cr 2 O 7 2− /CrO 4 2− ) aqueous solutions are same, which indicated that there was no coordination effect between Cr VI ions and NUM‐5 (Figure S14).…”
Section: Stability Characterization Of Num‐5mentioning
confidence: 95%
“…The result indicates that there is competitive absorption between Fe 3+ and CCP 1 ‐D, and the luminescence of CCP 1 ‐D is bound by Fe 3+ , resulting the luminescence quenching of CCP 1 ‐D. However, the absorption spectra of other metal ions do not overlap or are extremely small with the excitation spectrum of CCP 1 ‐D, so CCP 1 ‐D exhibits unique selectivity for iron ions . At last, the IR spectra comparison of 1 ‐D before/after the Fe 3+ sensing experiments also indicates that there is no interaction between Fe 3+ and CCP 1 ‐D (Figure S12, Supporting Information) .…”
Section: Resultsmentioning
confidence: 95%
“…They have attracted considerable attention for potential applications, especially for gas storage, [23] catalysis, [24] separation, [25] biomedicine, [26] sensing, [27] and enzyme immobilization. [28] Zeolitic imidazolate frameworks (ZIFs) are a class of MOFs in which tetrahedral metal centers (i. e. M = Zn 2 + , Co 2 + , and Cd 2 + ) are linked by imidazole (Im) or functionalized imidazole (RIm) ligands. [29] By combining metal ions with either Im or RIm, a large number of crystalline ZIFs have been prepared which have high thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%